ANALISIS FAKTOR INTENSITAS TEGANGAN (SIF) DENGAN VARIASI PANJANG RETAK PADA PELAT GELADAK UTAMA KAPAL “ MT. KLAWOTONG “ DENGAN MENGGUNAKAN METODE ELEMEN HINGGA (FEM) - Kiryanto, Kiryanto (TEKNIK, 2010)
Crack defect on main deck plate is source of failure ship structure. Small intensity of crack in the future canbe to large influence lateral force and bending moment. Crack defect characteristics can be to know shearintensity factor (SIF) on main deck is used mathematics simulation model based on fracture mechanics (FM)and finite element method (FEM). Goal of this research know characteristics main deck plate get a crack withload forces while deck plate start is loading until to crack propagation good stability.The MT Klawotong is chose in this research . Main deck plate is location as the sample. It is number 3 oncargo oil. Any analysis of data that is to counting of profile constructions, length strength, modeling withANSYS Version 9.0 and counting of shear intensity factor (SIF).Research on this structure failure result any substance that is, Sagging condition plate shears 50.34 MPa withsafety factor 8,939 crack long maximum is 0.02 m, value of shear intensity factor (SIF) KI WD. Pilkey = 12.615MPa m , KII WD. Pilkey = 0 MPa m , KI ANSYS = 13.,451 MPa m , KII ANSYS = 0.693 MPa m . Prosentaso oferror counting programe KI = 0.062 %, KII = 1% . The ather hand Hoging condition plate shears 15.08 MPawith safety factor 29.841 crack long maximum is 0 .3 m , value of shear intensity factor (SIF) KI WD. Pilkey=14.,645 MPa m , KII WD. Pilkey = 0 MPa m , KI ANSYS = 15.585 MPa m , KII ANSYS = 0.352 MPa m ,Prosentaso of error counting programe KI = 0.062 %, KII = 1%.